Práxis política no MST: produção de saberes e de sabedoria. - Silva, Rita de Cássia Curvelo da (2008)
The object of study of this thesis are the social struggles of the Landless Rural Workers Movement MST, conceived as a space for the production and accumulation of knowledge by young people and adults. The study sets out to explain the constitution of an educational process and the emergence of pedagogies seeking to construct new social beings by means of different forms of organization and collective action elaborated and made concrete by militants, leaders and the social base of the Movement. Based on the hypothesis that it is in the theoretical and practical processes of struggle that landless workers construct their own knowledge which whilst taking social practice as the starting point is dialectically interwoven with activities of political formation promoted by the MST. Starting from this premise the research propitiated an analysis of the production of knowledge by the landless workers, based on the thinking, feeling, desires and actions of these subjects and, in particular, on the political praxis which they develop. Whilst prioritising a qualitative research methodology, we made an option for the diversification of human types, with distinct life histories and trajectories in the MST, from different places in the country. Oral sources composed the chief resource for the research, based on the systematic collection of autobiographical narratives of people from all the states in which the MST is active, by means of the technique of semi-structured interviews, in addition to participant observation and the study of printed and audio-visual documents. As a result of the verbal interaction between the researcher and the young people and adults researched, we found evidence that these consolidate the knowledge they acquire in their political praxis, strengthened by other fundamental forms of prais, and construct new theoretical and practical knowledge, develop their affectivity, affirm their individual desires and form a collective desire. They take on the role of historical agents, with a leading part in the proletariat struggles for the transformation of society. The subjects knowledge, the change in the social relations which they experience and the struggles for alterations in the existential conditions of the working class are, however, processes permeated by many contradictions which contribute to the weakening of social movements like the MST and to the advance of mass struggle.